Differential association of air pollution exposure with neonatal and postneonatal mortality in England and Wales: A cohort study - Kotecha, Sarah J.; Watkins, W. John; Lowe, John; Grigg, Jonathan; Kotecha, Sailesh (PLOS Medicine, 2020)
Background Many but not all studies suggest an association between air pollution exposure and infant mortality. We sought to investigate whether pollution exposure is differentially associated with all-cause neonatal or postneonatal mortality, or specific causes of infant mortality. Methods and findings We separately investigated the associations of exposure to particulate matter with aerodynamic diameter ≤ 10 μm (PM10), nitrogen dioxide (NO2), and sulphur dioxide (SO2) with all-cause infant, neonatal, and postneonatal mortality, and with specific causes of infant deaths in 7,984,366 live births between 2001 and 2012 in England and Wales. Overall, 51.3% of the live births were male, and there were 36,485 infant deaths (25,110 neonatal deaths and 11,375 postneonatal deaths). We adjusted for the following major confounders: deprivation, birthweight, maternal age, sex, and multiple birth. Adjusted odds ratios (95% CI; p-value) for infant deaths were significantly increased for NO2, PM10, and SO2 (1.066 [1.027, 1.107; p = 0.001], 1.044 [1.007, 1.082; p = 0.017], and 1.190 [1.146, 1.235; p < 0.001], respectively) when highest and lowest pollutant quintiles were compared; however, neonatal mortality was significantly associated with SO2 (1.207 [1.154, 1.262; p < 0.001]) but not significantly associated with NO2 and PM10 (1.044 [0.998, 1.092; p = 0.059] and 1.008 [0.966, 1.052; p = 0.702], respectively). Postneonatal mortality was significantly associated with all pollutants: NO2, 1.108 (1.038, 1.182; p < 0.001); PM10, 1.117 (1.050, 1.188; p < 0.001); and SO2, 1.147 (1.076, 1.224; p < 0.001). Whilst all were similarly associated with endocrine causes of infant deaths (NO2, 2.167 [1.539, 3.052; p < 0.001]; PM10, 1.433 [1.066, 1.926; p = 0.017]; and SO2, 1.558 [1.147, 2.116; p = 0.005]), they were differentially associated with other specific causes: NO2 and PM10 were associated with an increase in infant deaths from congenital malformations of the nervous (NO2, 1.525 [1.179, 1.974; p = 0.001]; PM10, 1.457 [1.150, 1.846; p = 0.002]) and gastrointestinal systems (NO2, 1.214 [1.006, 1.466; p = 0.043]; PM10, 1.312 [1.096, 1.571; p = 0.003]), and NO2 was also associated with deaths from malformations of the respiratory system (1.306 [1.019, 1.675; p = 0.035]). In contrast, SO2 was associated with an increase in infant deaths from perinatal causes (1.214 [1.156, 1.275; p < 0.001]) and from malformations of the circulatory system (1.172 [1.011, 1.358; p = 0.035]). A limitation of this study was that we were not able to study associations of air pollution exposure and infant mortality during the different trimesters of pregnancy. In addition, we were not able to control for all confounding factors such as maternal smoking. Conclusions In this study, we found that NO2, PM10, and SO2 were differentially associated with all-cause mortality and with specific causes of infant, neonatal, and postneonatal mortality.